Building the Kitagawa-Takahashi diagram of flawed materials and components using an optimized V-notched cylindrical specimen. (1st February 2020) - Benedetti, M.; Santus, C.
Highlights: Kitagawa-Takahashi diagram built from SN curves of notched and plain samples. Concomitant effect of defect and notch stress gradient is considered. Interpretation of experimental data of additively manufactured Ti-6Al-4V. Matlab scripit to facilitate the usage of the present method. Abstract: The present technical note illustrates a novel procedure for building the Kitagawa-Takahashi diagram of a flawed material and of notched components made of the same material. The novelty of the method over the existing technical literature is the use of a rounded V-notched cylindrical specimen, whose geometry was optimized to maximize the intensity of the asymptotical notch stress term. In this way, the sensitivity to experimental uncertainties is reduced and no cumbersome fracture mechanics tests are requested to determine the crack threshold of the defect free of the defect-free material counterpart. The only experimental input are the high-cycle fatigue strength and the mean size of the critical defect at the notch tip of three specimen batches differing in the size of the critical defect and/or in the notch root radius. The potentiality of the method is checked for an additively manufactured Ti-6Al-4V alloy.